Language Teaching and Learning: Effective Strategies for Improving Language Competence - Syukur Berkat Zai; Destin Elsa Putri Ginting; Arozatulo Bawamenewi; Ester Ceria Gulo (Yayasan Adra Karima Hubbi, 2024)
Background. The language learning process must be accompanied by language skills strategies, namely listening, speaking, reading and writing skills. All these strategies are very important to improve language skills. With these strategies, the learning process will run well. Good language skills can help people interact and communicate with the people around them. Purpose. Along with the development of the times and technology, Indonesian is also an inspiration to be introduced and developed throughout the world. The technique used in data collection is to use the discussion lecture method, as well as the team teaching technique. Method. The purpose of this research is that a better language skills learning process can provide good results and achievements for students. Results. The results showed that with effective steps, teachers can use them to teach students' language competence and not only use the lecture learning model. Conclusion. Based on questionnaires that have been distributed to students, researchers obtained results that show that in learning Indonesian, especially language competence, the strategies used by researchers are effective.